Tracing the Roles of Nahdlatul Ulama (NU) and Muhammadiyah in the Stability of Islamic Education in Indonesia - Adawiyah, Robiatul (DAYAH: Journal of Islamic Education, 2026)
Islamic education plays an important role in shaping character, strengthening religious identity, and contributing to social development in Indonesia. The historical development of Islamic education has also been closely associated with Islamic mass organizations, particularly Nahdlatul Ulama (NU) and Muhammadiyah, since the early twentieth century. This study traces the historical and institutional trajectories of Islamic education in Indonesia through the roles of NU and Muhammadiyah and discusses how their educational orientations are linked to the continuity of the Islamic education system amid social change and global challenges. This study uses a library research design. The sources include scholarly books, journal articles, selected writings of central NU and Muhammadiyah figures, and organizational documents. The materials are examined using content analysis through close reading and thematic grouping to identify recurrent ideas, institutional strategies, and educational orientations reflected in the literature. The analysis indicates that Muhammadiyah contributes to the renewal of Islamic education through the integration of religious knowledge and modern science within structured educational institutions. NU, meanwhile, maintains pesantren-based traditions and develops formal institutions grounded in moderate values, ethical formation, and classical scholarship. These orientations are discussed as complementary rather than contradictory and are associated with continuity and sustainability in Indonesia’s Islamic education landscape. Strengthening educational institutions under NU and Muhammadiyah and re-actualizing the educational ideas of their key figures remain important in responding to the challenges of Islamic education in the context of Industry 4.0 and Society 5.0. Abstrak Pendidikan Islam berperan penting dalam pembentukan karakter, penguatan identitas keagamaan, dan kontribusinya terhadap perkembangan masyarakat Indonesia. Secara historis, perkembangan pendidikan Islam di Indonesia juga tidak terlepas dari peran organisasi kemasyarakatan Islam, khususnya Nahdlatul Ulama (NU) dan Muhammadiyah, sejak awal abad ke-20. Penelitian ini bertujuan menelusuri jejak historis dan kelembagaan pendidikan Islam di Indonesia melalui peran NU dan Muhammadiyah, serta membahas keterkaitan orientasi pendidikan keduanya dengan keberlanjutan sistem pendidikan Islam di tengah perubahan sosial dan tantangan global. Penelitian ini menggunakan desain penelitian kepustakaan (library research). Sumber data meliputi buku ilmiah, artikel jurnal, karya tokoh sentral NU dan Muhammadiyah, serta dokumen organisasi. Data dianalisis menggunakan analisis isi (content analysis) melalui pembacaan mendalam dan pengelompokan tema untuk mengidentifikasi gagasan, strategi kelembagaan, dan orientasi pendidikan yang berulang dalam literatur. Hasil kajian menunjukkan bahwa Muhammadiyah berkontribusi pada pembaruan pendidikan Islam melalui integrasi pengetahuan agama dan ilmu pengetahuan modern dalam lembaga pendidikan yang terstruktur. Sementara itu, NU mempertahankan tradisi keilmuan pesantren dan mengembangkan institusi formal yang berlandaskan nilai-nilai moderat, pembentukan etika, serta khazanah keilmuan klasik. Kedua orientasi tersebut dipahami sebagai saling melengkapi, bukan saling menegasikan, dan berkaitan dengan kesinambungan serta keberlanjutan pendidikan Islam di Indonesia. Penguatan kelembagaan pendidikan NU dan Muhammadiyah serta reaktualisasi pemikiran tokoh-tokohnya tetap penting untuk merespons tantangan pendidikan Islam dalam konteks Industri 4.0 dan Society 5.0.